Multimodal profiling of chordoma immunity reveals distinct immune contextures - van Oost, Siddh; Meijer, Debora M; Ijsselsteijn, Marieke E; Roelands, Jessica P; van den Akker, Brendy E M W; van der Breggen, Ruud; Briaire-de Bruijn, Inge H; van der Ploeg, Manon; Wijers-Koster, Pauline M; Polak, Samuel B; Peul, Wilco C; van der Wal, Robert J P; et al. (Journal for immunotherapy of cancer, 2024)
BackgroundChordomas are rare cancers from the axial skeleton which present a challenging clinical management with limited treatment options due to their anatomical location. In recent years, a few clinical trials demonstrated that chordomas can respond to immunotherapy. However, an in-depth portrayal of chordoma immunity and its association with clinical parameters is still lacking.MethodsWe present a comprehensive characterization of immunological features of 76 chordomas through application of a multimodal approach. Transcriptomic profiling of 20 chordomas was performed to inform on the activity of immune-related genes through the immunologic constant of rejection (ICR) signature. Multidimensional immunophenotyping through imaging mass cytometry was applied to provide insights in the different immune contextures of 32 chordomas. T cell infiltration was further evaluated in all 76 patients by means of multispectral immunofluorescence and then associated with clinical parameters through univariate and multivariate Cox proportional hazard models as well as Kaplan-Meier estimates. Moreover, distinct expression patterns of human leukocyte antigen (HLA) class I were assessed by immunohistochemical staining in all 76 patients. Finally, clonal enrichment of the T cell receptor (TCR) was sought through profiling of the variable region of TCRB locus of 24 patients.ResultsChordomas generally presented an immune “hot” microenvironment in comparison to other sarcomas, as indicated by the ICR transcriptional signature. We identified two distinct groups of chordomas based on T cell infiltration which were independent from clinical parameters. The highly infiltrated group was further characterized by high dendritic cell infiltration and the presence of multicellular immune aggregates in tumors, whereas low T cell infiltration was associated with lower overall cell densities of immune and stromal cells. Interestingly, patients with higher T cell infiltration displayed a more pronounced clonal enrichment of the TCR repertoire compared with those with low T cell counts. Furthermore, we observed that the majority of chordomas maintained HLA class I expression.ConclusionOur findings shed light on the natural immunity against chordomas through the identification of distinct immune contextures. Understanding their immune landscape could guide the development and application of immunotherapies in a tailored manner, ultimately leading to an improved clinical outcome for patients with chordoma.